2007
DOI: 10.1086/519524
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Variable Stars inCOROT's First Main Observing Field (LRc1)

Abstract: The COROT space mission will monitor several target fields for up to 150 days to perform asteroseismology and to search for extrasolar planets by photometric transits. Variable stars in the target fields are important objects for additional scientific studies but can also disturb the search for planetary transits. A variability characterization of the target fields prior to COROT observations is therefore important for two reasons: to find interesting variable stars to monitor further and to make an analysis o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 17 publications
(32 reference statements)
1
31
0
Order By: Relevance
“…The scientific task of the detection teams is to provide a characterized set of planetary transiting candidates; although as a natural by-product they build a list of identified eclipsing binaries which is provided here. Some of the binaries (such as E1_1922, E2_0170, E2_1450, E2_3052, E1_1262, and E2_0169) have already been observed by Karoff et al (2007) within the Berlin Exoplanet Search Telescope (BEST) survey of variable stars in the CoRoT fields. Among the binaries in the list, the following are clearly eccentric: E1_1273, E1_1352, E1_1422, E1_2978, E1_3418, E1_3671, E1_4583, E1_5097, E1_5173, E2_0258, E2_0667, E2_1661, E2_1954, E2_2257, E2_2631, E2_2871, E2_3956, E2_3995, E2_5245.…”
Section: Resultsmentioning
confidence: 99%
“…The scientific task of the detection teams is to provide a characterized set of planetary transiting candidates; although as a natural by-product they build a list of identified eclipsing binaries which is provided here. Some of the binaries (such as E1_1922, E2_0170, E2_1450, E2_3052, E1_1262, and E2_0169) have already been observed by Karoff et al (2007) within the Berlin Exoplanet Search Telescope (BEST) survey of variable stars in the CoRoT fields. Among the binaries in the list, the following are clearly eccentric: E1_1273, E1_1352, E1_1422, E1_2978, E1_3418, E1_3671, E1_4583, E1_5097, E1_5173, E2_0258, E2_0667, E2_1661, E2_1954, E2_2257, E2_2631, E2_2871, E2_3956, E2_3995, E2_5245.…”
Section: Resultsmentioning
confidence: 99%
“…project (Kabath et al 2007;Karoff et al 2007;Kabath et al 2008Kabath et al , 2009bKabath et al , 2009aRauer et al 2010).…”
Section: Reduction Pipelinementioning
confidence: 99%
“…Deeg et al 2000;Martín et al 2001;Zapatero Osorio et al 2004;Steinfadt et al 2008;Deeg et al 2008;Rabus et al 2009), a module that derives observed on-off brightness differences has been added for the CoRoT follow-up. Furthermore, it includes a calculation of the contamination factors k c from a simulated CoRoT (Kabath et al 2007;Karoff et al 2007;Kabath et al 2008Kabath et al , 2009bKabath et al 2009a;Rauer et al 2009) which are routinely checked against the detections from CoRoT. They will also be used for future surveying of CoRoT-short run fields.…”
Section: "Vaphot/vanaliz" a Timeseries Photometry Package With An Anmentioning
confidence: 99%